DETERMINAN KEPUASAN KERJA DAN DAMPAKNYA PADA KINERJA PEGAWAI PADA DIREKTORAT KEPELABUHAN - Daulay, Achmad Muzairi; Yusuf, M. (Media Riset Bisnis Ekonomi Sains dan Terapan, 2025)
This study aims to examine and analyze the influence of communication and work discipline on employee performance, with job satisfaction as an intervening variable at the Directorate of Ports. The research employs an associative method with a quantitative approach. The sample consists of 64 respondents, selected using a random sampling technique. The analysis method used is SEM-PLS. The findings of the study reveal that communication has no positive and significant effect on job satisfaction; work discipline has a positive and significant effect on job satisfaction; communication has a positive and significant effect on employee performance; work discipline has no positive and significant effect on employee performance; job satisfaction has a positive and significant effect on employee performance; communication has no significant indirect effect on employee performance through job satisfaction; and work discipline also has no significant indirect effect on employee performance through job satisfaction.Keywords: Work Communication, Work Discipline, Job Satisfaction, Employee Performance